The evaluation of the quality of teaching in the university: A review of the literature - María Isabel Ramírez Garzón; Juny Montoya Vargas (Universitat Politècnica de València, 2014)
This  article  provides  a  general overview of the literature about faculty evaluation. The review process begins from the main challenges that have been found in different publications, research reports and literature, where faculty evaluation has been addressed by its conceptions,  purposes,  approaches and  instruments.  Through  this  lens four aspects has been considered: the complexity of the teacher activity, the lack of agreement towards what to be a good teacher at university is, to limit the  teacher's  responsibility  only  to student learning, and the growth of the criteria for teaching evaluation. These criteria could be materialized in some perspectives  about  "good  teaching". The review offers a clear idea of the state of the art regarding faculty evaluation research. It gives elements of analysis for  the  development  of  research  in the  future.  The  paper  concludes  by describing  a  comprehensive,  open and  flexible  approach  to  teaching evaluation.  In  addition,  we  describe some foundations for the development of this approach.